Elucidating the controversial Drosera montana complex (Droseraceae): a taxonomic revision - Rivadavia, Fernando; Gonella, Paulo Minatel; Sano, Paulo Takeo; Fleischmann, Andreas (Phytotaxa, 2014)
The species of the affinity of Drosera montana (Droseraceae) are reviewed taxonomically and the complex is redefined to include only D. montana, D. tentaculata, D. tomentosa var. tomentosa, D. tomentosa var. glabrata, and D. spirocalyx. The latter is a newly described narrow endemic species from the Serra do Cipó in central Minas Gerais state, Brazil. The morphological characters distinguishing these five taxa from each other and from other similar species are discussed together with habitat and ecological information. Detailed illustrations, photographs, distribution maps and an identification key are provided. A lectotype for D. tomentosa is here designated.